Photo exemplars classification : the integration photographic history into photographic technique - Iwan Zahar (2014)
The dispute has been long whether photographic lecturers should integrate the history of photography into a course on photography. The photographic lectures should discuss photographic theory deeply, by introducing photographers such as henry Cartier Bresson, Cindy Sherman, Barbara Kruger etc to students. Most of the photographic lectures were more interested in teaching photographic techniques than photographic theory. This paper used content analysis to classify or categorize modernist photograph. The evaluation of photo used Barrett's critism model. The research used aesthetic exemplars in the form modernist photographers, or from Alfred Stieglitz to Rabubir Singh. Most of students were easily to relate with modernist photographers compared to postmodertnist photographers. The students were unfamiliar with subject matter, theme and photos presentation, thus they become difficult interpret postmodernist photo. Moreover, students were more interested in photographic techniques which were used by modernist photographers. The classification of photos will help lecturers to prepare for photographic courses especially for the beginnner